PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN MOTIVASI BELAJAR IPS SISWA KELAS VII SMPN 6 TANAH PUTIH - Sri Wahyuni; Sri Kartikowati; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: In general, social studies are taught using lecture and question and answer with the involvement of students in the learning process was minimal. Consiquencyt, students are not motivated to keep learning as expected by teachers So many students do not pay attention when the teacher explains the lesson, is not eager to ask or answer questions from teachers and do not want to know about what is conveyed by the teacher. Additionally, when the teacher gives the task, there are many students who do not do the work. It inlah which shows students' motivation in learning is very low. To that end, efforts should be made improvements in the learning process by selecting the appropriate teaching methods and appropriate for use. So students have the motivation to participate in every stage of learning. The aim of the study was to increase the motivation of social studies students of class VII in SMP N 6 Tanah Putih by using cooperative learning model make a match. This research was conducted in SMP N 6 Tanah Putih. The sample used in this study were students of class VII consists of 24 students. Data was collected using observation sheet teacher activity, student activities, student motivation and achievement test. Data analysis techniques in this study using the technique teacher activities, student activities and student motivation. From the analysis done shows cooperative learning model make a match proved to increase motivation to learn, especially in the IPS study Bisang class VII N 6 Tanah Putih.Keywords: PPD Learning Method, Student Motivation